STRATEGI PENGEMBANGAN USAHA PADA BISNIS SOTO LAMONGAN PAK DI DENGAN PENDEKATAN ANALISIS SOAR - Ahmad Zulfan Ghifari; Aries Kurniawan (JURNAL LENTERA BISNIS, 2025)
This study discusses the business development strategy of Soto Lamongan Pak Di using the SOAR analysis approach. The aim of this research is to identify the strengths, opportunities, aspirations, and results of the soto business, which has been established since 1970. The method used is qualitative with a phenomenological approach, through interviews with the owner and employees. The results indicate that Soto Lamongan Pak Di has authentic recipes and friendly service as its main strengths. Growth opportunities lie in the increasing interest of the public in traditional food. The long-term aspiration is to become a widely recognized soto restaurant while maintaining family values. The expected outcomes include increased customer loyalty and sustainable revenue growth. This study recommends developing menu variations to meet the trends of healthy eating.